Inside BAR (The Biblical archaeology review, 1984)
BAR is very pleased and proud to publish Yigael Yadin’s first extensive, popular account of the latest to be discovered and the longest of the Dead Sea Scrolls. We are grieved and saddened, however, that this account is being published posthumously. Yadin died of a heart attack on June 28. The article, "The Temple […]